Typhoo Tea and Victorinox Knives: Faroese Homemaking in a Foreign Country - Sólja Oyvindardóttir av Skarði 1991- (2018)
This is an ethnological study of homemaking in a new country. When you move to a new country, you at the same time leave another country behind. The focus in the thesis is on how Faroese people engage with migration and life in Iceland through objects and homemaking. The thesis is built on eight interviews in addition to previous research on the topic. Four of the narrators were Faroese while the other four were from Croatia, Poland and Turkey, which made it possible to compare Faroese homemaking to homemaking among other foreigners in Iceland. An important part of making a home in a new country is to bring objects from the home country. These objects are divided into two categories in the thesis: emotional objects and practical objects. Emotional objects can bring back fond memories and remind us of important people in our lives. Practical objects make life in the new place easier. The nostalgic feeling triggered by objects, and not least, by food and food products is also an important part of homemaking in a foreign country. Therefore, homemade as well as industrially produced food is being imported to Iceland, and specialities from the immigrants’ countries of origin are also made in Iceland. What especially distinguished the Faroese homes from the other foreign homes in this research project was the so-called Faroese corner, a corner or a wall especially dedicated to Faroese art and objects, which made the Faroese identity easy to spot in the Faroese homes in Iceland.